PREPARATION OF THIN FILMS FROM MULTI-LAYER 2D NANOMATERIALS LIQUID - Mahmood, Ari M.; Ibrahem, Mohammed A. (Science Journal of University of Zakho, 2023)
Thin films comprised of laminated 2D nanomaterials have garnered considerable attention and hold significant promise across a multitude of applications, driven by their exceptional and distinct attributes. This study presents an innovative approach for fabricating thin films on glass substrates through the utilization of 2D multilayer liquid nanomaterials via a sputtering technique. These nanomaterials, encompassing graphene, MoS2, and h-BN, were synthesized employing a common household blender, followed by dispersion in a range of solvents, including acetone, ethylene glycol, and deionized water. In-depth characterization of the resultant thin films was undertaken, employing a comprehensive suite of microscopic and spectroscopic analytical methodologies. The outcomes of these characterizations underscore the profound influence of both the selected bulk material and the choice of solvent on the structural and morphological properties of the thin films. Impressively, the prepared thin films exhibit superlative adhesion and uniformity, manifesting smooth surfaces and a remarkable degree of crystallinity. Through the judicious selection of diverse bulk materials and solvents, this study effectively demonstrates the unparalleled versatility and adaptability of the sputtering method in producing thin films with a wide spectrum of tailored properties. This research not only advances our understanding of thin film formation but also underscores the immense potential of 2D nanomaterial-based films in diverse technological applications.